INFLUENCES OF TOOL PIN PROFILE ON MECHANICAL PROPERTIES OF AA6061-T6 ALUMINUM PLATE JOINTS ON FRICTION STIR WELDING PROCESS - Hafiz, Rahmat
The Welding Institute (TWI) introduced a new method of solid-state welding in 1991 in Great Britain known as friction stir welding (FSW). FSW has been used as an alternative to joining aluminum materials which are difficult to weld using conventional methode like fusion welding. FSW is considered capable to produce better welded joints compared to fusion welding process, although defects such as void are often found in FSW welded joints. The voids are caused by material that cannot fill the empty space when the tool pin is moved. It can cause crack initiation when the joint is under load. The use of the appropriate type of pin is expected to reduce the risk of defects, especially voids. This study will observe the effect of variations in the shape of the pin profile on the quality of the FSW welded joints to avoid void defects. The types of pins used in this study are tapered cylinder, tapered with flats, and tapered thread cylinder. While the type of joint that used is a butt joint and uses AA6061-T6 material with a thickness of 8 mm. Welding was carried out at 1200 rpm and welding speed of 21.5 mm/minute. The resulting welding joints were tested including visual inspection, tensile test, metallographic and hardness tests using the microvickers hardness test to see the mechanical properties of the joints. The type of pin that can produce a good joint and have no defects is a tapered pin with flats. The welded joints that use this type of pin have the highest tensile strength (UTS) is 148 MPa or 43% of joint efficiency. It is free from welding defects, especially voids. Meanwhile, in the welding joints using tapered cylinder pins and tapered thread cylinders, internal defects such as voids were still found. From the observation of the microstructure of the welding process produces areas known as HAZ, TMAZ and WN. In each of these areas, the distribution of Mg2Si precipitate is even. The results of the hardness test in the welded area (HAZ, TMAZ, WN) show a decrease in the hardness value compared to the BM hardness value, which is between 46 to 53 HV.